A Z-scheme visible-light-driven Ag/Ag3PO4/Bi2MoO6 photocatalyst: synthesis and enhanced photocatalytic activity. Issue 127 (11th December 2015) - Lin, Xue; Hou, Jing; Jiang, Shanshan; Lin, Zhe; Wang, Miao; Che, Guangbo
Abstract : A novel Z-scheme Ag/Ag3 PO4 /Bi2 MoO6 photocatalyst was successfully synthesized. Ag/Ag3 PO4 /Bi2 MoO6 hybrid photocatalyst exhibited enhanced photocatalytic activity. Abstract : A Ag/Ag3 PO4 /Bi2 MoO6 hybrid was successfully prepared for the first time via an in situ precipitation method. The as-prepared Ag/Ag3 PO4 /Bi2 MoO6 hybrid included Ag3 PO4 nanoparticles (NPs) as well as Ag NPs assembling on the surface of Bi2 MoO6 nanosheets. Under visible light irradiation ( λ > 420 nm), the Ag/Ag3 PO4 /Bi2 MoO6 hybrid photocatalyst degraded rhodamine B (Rh B) efficiently and showed much higher photocatalytic activity than pure Ag3 PO4, Bi2 MoO6, Ag/Ag3 PO4, Ag/Bi2 MoO6, or Ag3 PO4 /Bi2 MoO6 . It was elucidated that the excellent photocatalytic performance of Ag/Ag3 PO4 /Bi2 MoO6 for the degradation of Rh B under visible light could be ascribed to the efficient separation of photogenerated electrons and holes through the Z-scheme system composed of Ag3 PO4, Ag and Bi2 MoO6, in which Ag NPs acted as the charge transmission-bridge. The quenching effects of different scavengers illustrated that O2 ˙ − and h + played the major role in Rh B degradation.